Nilai kearifan lokal pada lagu Lampung - Windo Dicky Irawan; Yasinta Mahendra; Junaidi Junaidi (Aksara: Jurnal Bahasa dan Sastra, 2021)
Local wisdom is a value that is a role model for the people of Lampung. These values are used as guidelines and a way of life for the people of Lampung. In addition, values are also things that must be pursued in order to have a better life. Therefore, cultural experts place the highest cultural value. The values of local wisdom in the people of Lampung are called piil pesenggiri which consists of meeting nyimah, nengah nyappur, sakai sambaian, and nickname adek. These values are implied in all aspects of life, including the popular Lampung songs. This article aims to describe the local wisdom values of the Lampung area in popular Lampung songs. Keywords: Local Wisdom, Piil Pesenggiri, Lampung.